1998
DOI: 10.1039/a805985c
|View full text |Cite
|
Sign up to set email alerts
|

A hydration-controlled nano-valve in a zeolite?†

Abstract: Ion-exchange and dehydration in clinoptilolite are simulated revealing a novel feature, a hydration-controlled nanovalve, which explains hitherto anomalous behaviour of this important zeolite system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The resulting average Ca coordination number is four with an average CaÈO distance of 2. 35 Experimental CaÈO dis-Ó. tances are longer (ca.…”
Section: Extra-framework Cation Positionsmentioning
confidence: 99%
“…The resulting average Ca coordination number is four with an average CaÈO distance of 2. 35 Experimental CaÈO dis-Ó. tances are longer (ca.…”
Section: Extra-framework Cation Positionsmentioning
confidence: 99%
“…We now wish to determine the role of water in controlling both the distribution of Si and Al within the framework and the location of efcs. The limited number of theoretical studies of hydrated zeolites have considered only the location and dynamics [7][8][9][10] of water in fixed, ordered or 'random' distributions of Al.…”
mentioning
confidence: 99%
“…calcination (typically to 623 K), and ®nally thermal destruction (typically 1273 K). The ®rst study was on a mixed Ca,K-cation system and demonstrated the combination of three techniques: high-resolution powder X-ray diffraction, Ca,K-EXAFS and Grand Canonical Monte-Carlo-type computer simulations by which the cation/water content could be varied in order to elucidate likely cation locations as the dehydrated/activated structure was approached; this indicated a valve-type mechanism in which gaseous¯ow through the zeolite is restricted in either direction by the K cations projecting into the main zeolite channel (O'Connor et al, 1998). The main problem in this study was the poor quality of available clinoptilolite powders: the natural minerals have poor crystallinity whereas the few successfully synthesized versions are multi-phasic, and so the main value of the complementary methods here was rather to compensate for the restricted quality of the experimental data.…”
Section: Figurementioning
confidence: 99%